Modified therapy concepts for fragility fractures of the pelvis after additional MRI - Graul, Isabel; Marintschev, Ivan; Hackenbroch, Carsten; Palm, Hans-Georg; Friemert, Benedikt; Lang, Patricia (PLoS ONE, 2020)
Background Fractures of the pelvic ring in elderly patients have increased in frequency over time. These injuries are associated with a high morbidity and have a socio-economic impact. The diagnostic procedures and their influence of therapy decisions are still controversial. Methods In a retrospective study, we investigate the value of additional MRI examination on therapy decision of fragility fractures of the pelvis. The evaluation of all patients with pelvic fractures without adequate trauma and with performed CT and MRI was conducted at three large German hospitals. The imaging procedure took place within a maximum interval of 4 weeks. After evaluation of the imaging, the resulting therapeutic consequences either based on CT alone or on CT and MRI were reviewed by experienced pelvic surgeons. Results Of 754 patients with pelvic injuries, 67 (age 80 +/- 9.7 years, f: m 54:13) could be included. The detection of vertical fractures in CT (n = 40 unilateral, n = 11 bilateral) could be increased by the additional MRI (n = 44 unilateral, n = 23 bilateral). A horizontal fracture component was identified in CT in 9.0% (n = 6) vs. MRI in 25.4% (n = 17) of the cases. An anterior pelvic ring injury was detected in 71.6% (n = 44; 4x bilateral) in CT, in 80.6% in MRI (n = 50, 4 bilateral). Additive MRI imaging increased the decision rate for surgical therapy from 20.9% (n = 14) to 31.3% (n = 21). Conclusions The results of this study further support the value of bone marrow edema detection by MRI diagnostics (or dual source CT which showed promising initial results) for the detection of pelvic ring fractures. For the first time, the study identifies an additional therapeutic consequence by an increased rate of surgical procedures.
CRIS-Team Scopus Importer:2020-10-23